2015
DOI: 10.1002/ajpa.22829
|View full text |Cite
|
Sign up to set email alerts
|

Exudativory in the Asian loris, Nycticebus: Evolutionary divergence in the toothcomb and M3

Abstract: The more robust, "squared off" toothcomb in Nycticebus matches behavioral observations that these primates gouge to access exudates. Results of the present study indicate that the toothcomb is the likely candidate for the dental tool used in gouging. The size reduction of the lower last molar in Nycticebus, a trait also found in a previous study in exudativorous galagos, may indicate that there is reduced selective pressure in a diet where little mastication would be needed to mechanically process exudates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…(Nekaris 2014). The same specializations are clear in marmosets and have arisen through convergent evolution (Burrows et al 2016).…”
Section: Obligate Gum Feedersmentioning
confidence: 78%
See 1 more Smart Citation
“…(Nekaris 2014). The same specializations are clear in marmosets and have arisen through convergent evolution (Burrows et al 2016).…”
Section: Obligate Gum Feedersmentioning
confidence: 78%
“…Obligate feeders must have the capability of inducing the production of gum, with a well-developed dentition adapted to damage a tree or liana severely enough for it to produce gum, a process called gouging. All exudativores have evolved specialized dentition to gouge and harvest gum (Coimbra-Filho & Mittermeier 1977;Ravosa et al 2010;Burrows et al 2016). The upper first premolars are used as an anchor for the teeth on the upper mandible to scrape the cambium away, stimulating gummosis (Nussinovitch 2009).…”
Section: Obligate Gum Feedersmentioning
confidence: 99%
“…For example, dentition within primates that are primarily seed-eaters, gum and sap-eaters, and fruit feeders shows unique morphological features linked to acquiring and processing these particular foods (e.g. Hylander, 1975;Lambert et al 2004;Burrows & Nash, 2010;Burrows et al 2015). Mandibular morphology has similarly been linked to dietary niche across a range of primate taxa (e.g.…”
Section: Ecomorphological Relationships In Primate Mimetic Musculaturementioning
confidence: 99%
“…; Burrows & Nash, ; Burrows et al. ). Mandibular morphology has similarly been linked to dietary niche across a range of primate taxa (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Slow lorises display a suite of morphological adaptations that are centered on exploiting exudate food sources, and it is now widely accepted to categorize them as exudativorous primates (Burrows, Harstone-Rose, & Nash, 2015). Although originally suggested to be frugivorous based on comparisons with pottos (Charles-Dominique, 1977), wild field studies have clearly demonstrated that slow lorises (Nycticebus) are specialized exudativores (gum specialists) (Nekaris, 2014).…”
mentioning
confidence: 99%